Video education to improve clinical skills in the prevention of and response to vasovagal syncopal episodes - Anne Coakley, BS; Alison Bailey, MD; Joy Tao, MD; Yujie L. Liou, DO; Amanda Champlain, MD; Michael Ander, MD; Eden Lake, MD (Wolters Kluwer, 2020)
Background: Vasovagal syncope is a common clinical occurrence during routine outpatient dermatology procedures, such as injections and biopsies. Despite its prevalence, many medical students and health care professionals do not know how to respond appropriately to a syncopal episode. Objective: The aim of this study was to determine the efficacy of a health education video in teaching medical students and health care professionals the appropriate management steps for vasovagal syncope and its prodromal symptoms in a clinical setting. Methods: With input from dermatologists and an anesthesiologist, an instructional video was developed to demonstrate basic management for a presyncopal and syncopal patient. A pre- and post-video quiz was used to assess comprehension. A total of 124 medical students and health care professionals were enrolled in this study. Results: After viewing the video, the proportion of respondents who were able to correctly identify how long to monitor a patient after a syncopal episode increased from pre- to post-intervention (44% vs. 71%; p < .001). Participants expressed higher levels of agreement with the statement "I am aware of the appropriate steps in managing a patient during an episode of vasovagal syncope" after the intervention (p < .001). Respondents reported increased confidence in managing a patient during a syncopal episode after this intervention (p < .001). Conclusion: These results suggest that this health education video is a useful tool for educating medical students and nursing professionals about the management of vasovagal syncope in a clinical setting. We propose the use of video education as an efficient means of increasing recognition and standardizing therapeutic response to the prodromal symptoms of syncope and syncopal episodes.